1990
DOI: 10.1016/0014-5793(90)81527-u
|View full text |Cite
|
Sign up to set email alerts
|

Footprinting studies on the sequence‐selective binding of pentamidine to DNA

Abstract: The sequence-selective binding of pentamidine, an antimicrobial aromatic diamidine, has been investigated by footprinting studies on two different DNA fragments using DNase I, micrococcal nuclease and hydroxyl radical as probes. Each probe reveals drug-induced protection from cleavage in AT-rich regions. The best binding sites consist of at least 5 consecutive AT base pairs. Three or less AT pairs do not constitute a pentamidine binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 12 publications
5
31
0
Order By: Relevance
“…the DNA within the A+T-rich minor groove, as had been previously suggested for pentamidine from footprinting studies (Fox et al, 1990). From an examination of these two structures, we have been able to establish a rational basis for the superior DNA-binding ability of propamidine as compared with pentamidine.…”
Section: Fig 2 the Y-oxapentamidine-d(cgcgaattcgcg) Complex (Left)mentioning
confidence: 52%
“…the DNA within the A+T-rich minor groove, as had been previously suggested for pentamidine from footprinting studies (Fox et al, 1990). From an examination of these two structures, we have been able to establish a rational basis for the superior DNA-binding ability of propamidine as compared with pentamidine.…”
Section: Fig 2 the Y-oxapentamidine-d(cgcgaattcgcg) Complex (Left)mentioning
confidence: 52%
“…Diamidines such as pentamidine, 4',6-diamidino-2-phenylindole, and berenil have been shown to bind preferentially to A+T-rich regions in minor grooves of B-DNA without intercalating between base pairs (12,28,32,34,38). The preferential binding of diamidino compounds to A+T-rich regions is further confirmed by the disruption of A+T-rich kinetoplastic DNA in leishmania (7) and trypanosomes (33).…”
Section: Resultsmentioning
confidence: 93%
“…It has been suggested that these compounds interfere with nucleic acid synthesis and/or metabolism (16,40,44). Pentamidine and other diamidines, such as 4',6-diamidino-2-phenylindole and berenil, have been shown to bind to DNA and exhibit a preference for binding to A+T-rich regions in the minor groove of B-DNA (12,28,32,34,38). To assess their range of activity further and better understand the mechanism(s) of antimicrobial action, we examined the structure-activity relationships of pentamidine and 38 analogs of pentamidine in an in vitro assay against G. lamblia WB (ATCC 30957) and correlated the antigiardial activities of these dicationic molecules with their DNA-binding affinities.…”
mentioning
confidence: 99%
“…Because of their high sequence specificity, they are rarely used and often considered as poor footprinting reagents. They have been tested mostly against AT-specific ligands (7,21,37,38). We find that these enzymes can, under the right circumstances, yield extremely interesting complementary information in the case of non-strictly AT-specific ligands; in some ways they are particularly well adapted for footprinting lexitropsins.…”
Section: Discussionmentioning
confidence: 99%